2022
DOI: 10.3390/coatings12010105
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Wear Resistance of a Cr7C3 Reinforced Ni3Al Composite Coating Prepared by Laser Cladding

Abstract: Using Cr7C3/Ni3Al alloyed powder and Cr3C2/Ni3Al mixed powder, laser cladding was carried out to prepare a Cr7C3 reinforced Ni3Al composite cladding layer. The microstructure and tribological properties of the cladding materials were investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), transmission electron microscopy (TEM), and wear tests. The results indicate that the microstructure of the Cr7C3/Ni3Al alloyed powder cladding layer contains mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…When the power was high, the size of Cr 7 C 3 became coarse, the area of Cr 7 C 3 was relatively low, and the distribution of Cr 7 C 3 was irregular. Related studies have shown that the carbide size has a certain influence on the wear resistance mechanism of the laser cladding layer [16]. In the friction process, large Cr 7 C 3 particles can effectively separate the grinding pair and reduce the friction coefficient and friction shear force.…”
Section: Microstructure and Phase Composition Of The Laser Cladding L...mentioning
confidence: 99%
See 1 more Smart Citation
“…When the power was high, the size of Cr 7 C 3 became coarse, the area of Cr 7 C 3 was relatively low, and the distribution of Cr 7 C 3 was irregular. Related studies have shown that the carbide size has a certain influence on the wear resistance mechanism of the laser cladding layer [16]. In the friction process, large Cr 7 C 3 particles can effectively separate the grinding pair and reduce the friction coefficient and friction shear force.…”
Section: Microstructure and Phase Composition Of The Laser Cladding L...mentioning
confidence: 99%
“…Thus, a laser cladding layer with good wear resistance and high microhardness was obtained. Liu et al [16] used a Ni 3 Al + Cr 3 C 2 mixed powder and a Ni 3 Al/Cr 7 C 3 alloy powder to perform a laser cladding experiment, and the results showed that the microstructure of the laser cladding layer was uniform and dense, without defects, and showed metallurgical bonding with the substrate. Due to the high laser energy density and the fast cooling rate of the laser cladding layer, laser cladding technology has the effect of grain refinement and solution strengthening.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that Cr 3 C 2 can serve as an excellent strengthening phase for composite materials and can improve the performance of alloys. Liu et al [18] prepared a Ni 3 Al/Cr 3 C 2 -composite wear-resistant coating on a 42CrMo base material, and proposed a wear model of the composite material based on the results of experiments on friction and wear. This model proposes a softer Ni 3 Al phase as the base, with harder carbide particles embedded in it.…”
Section: Introductionmentioning
confidence: 99%